Exploring the reflective practice of Anglican laity: finding manna in the desert. Issue 4 (4th July 2021) - Dunlop, Sarah; Nancekievill, Catherine; Ross-McCabe, Pippa
ABSTRACT: This article reports the findings of a small-scale qualitative research project to discover how lay people within the Church of England process significant and everyday life events in light of their Christian faith. Our aim was to resource knowledge about how theological reflection skills can be developed both within the informal parish setting and during formal theological education for licensed ministry. We analysed data from semi-structured, photo elicitation interviews using the 'defining features' of theological reflection at its best, adapted from Ross-McCabe ([2020]. "Straw for the Bricks at Last? Theological Reflection Under the Common Awards." Practical Theology 13 (4): 413–426). We found that people predominantly theologically reflect via an awareness of God's presence which supports the processing of a situation. Most often, people took their internal theological framework as complete and analysed their critical incident against this. We identified several areas that could be developed in order to strengthen theological reflection: deeper engagement with Christian tradition, critical engagement with Scripture and dialogical approaches to God's presence. Additionally, openness to the possibility of change could deepen the transformative potential of this processing.